Investigation of spiritual and emotional intelligence on academic performance among pakistan students - Anita, Abdul Rani; Jamshid, Ali Turi; Imaduddin, Abidin (2018)
Continuous learning works like a blood for organization and individuals to proceed and succeed. Academic prosperity depends upon student's enthusiastic attitude and their emotional and spiritual intelligences. This study was conducted in learning organizations to see the impact of these two constructs on academic performance using cross-sectional questionnaire based survey to 113 students in Pakistan. The findings provide positive and significant correlations among the types of intelligences and academic performance. Data was analyzed using SPSS and the results were verified using statistical methods like correlation, regression, ANNOVA, Cronbach alpha and means. This study highlights the role of emotional intelligence and spiritual intelligence and found it is the most demanding and have significant effect on academic performance, therefore, it needs better integration in academic practices, routine and culture.